2009
DOI: 10.1093/her/cyp066
|View full text |Cite
|
Sign up to set email alerts
|

'Smoking': use of cigarettes, cigars and blunts among Southeast Asian American youth and young adults

Abstract: Increased use of cigars has been noted among youth, as well as use of blunts (hollowed-out cigars filled with marijuana). Three types of relationships have been previously hypothesized between use of tobacco and marijuana in substance use progression. We aimed to assess these relationships for Southeast Asian American youth and adults in an urban population. We conducted in-person interviews with 164 Southeast Asians, smokers and nonsmokers, in two low-income urban communities in Northern California, collectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 46 publications
(42 reference statements)
2
48
1
Order By: Relevance
“…A possible explanation for gateway-like progressions from one drug to others is transfer of learning, in which established drug-seeking behavior comes to be reinforced by the effects of a different drug. This kind of effect seems likely in the case of cannabis and tobacco due to shared features of the behavioral chains involved in smoking these substances (Lee et al, 2010). However, the gateway-like effect observed in the present study did not involve transfer of learning, since the rats received THC passively.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…A possible explanation for gateway-like progressions from one drug to others is transfer of learning, in which established drug-seeking behavior comes to be reinforced by the effects of a different drug. This kind of effect seems likely in the case of cannabis and tobacco due to shared features of the behavioral chains involved in smoking these substances (Lee et al, 2010). However, the gateway-like effect observed in the present study did not involve transfer of learning, since the rats received THC passively.…”
Section: Discussioncontrasting
confidence: 51%
“…It should also be noted that rats did not receive THC and nicotine simultaneously in the present study, but that the results might still be relevant to simultaneous use. Tobacco and cannabis are often coadministered because users believe that nicotine potentiates the effects of cannabis (Amos et al, 2004;Lee et al, 2010). Such co-administration could encourage a progression from cannabis to tobacco by a number of mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, Scherma et al [74] found that THC potentiated the effects of a sub-threshold dose of nicotine; that is, this dose of nicotine failed to induce a significant CPP when tested alone, but induced a significant CPP after pretreatment with THC during the acquisition phase. This finding is consistent with the fact that humans often combine nicotine and THC (in the form of cannabis) to obtain an enhanced rewarding effect [75,76].…”
Section: Role Of Cb 1 Receptors In Nicotine Addictionsupporting
confidence: 87%
“…15 Blunt smokers often identify themselves as marijuana users but not as tobacco users, which may have led to underestimates of population of LCC consumption. [15][16][17] Thus, in recent years, there has been an increased scientific interest in the relationships between tobacco and marijuana use among youth and young adults in regard to the direction of uptake pathways. Since both substances are typically smoked, tobacco and marijuana use may support and reinforce use of each other.…”
Section: Introductionmentioning
confidence: 99%